Quantification of Pyrethroid Residue in Food, Agricultural and Biological Samples - Shukla, Madhurani; Tiwari, Kishore K. (Asian Journal of Chemistry, 2018)
A simple and highly sensitive spectrophotometric method has been developed for the quantification of broadly used pyrethroid pesticides i.e. cypermethrin and fenvalerate. The developed method is based on alkaline hydrolysis of these pyrethroid pesticides to cyanide ion. The cyanide ion is further react with potassium iodide in acidic medium to liberate iodine and this liberated iodine oxidizes leucomalachite green to malachite green. The absorption maximum of the formed dye is measured at 600 nm. Beer’s law is obeyed in the concentration range of 0.08-0.72 and 0.16-0.88 μg/mL for cypermethrin and fenvalerate, respectively. The molar absorptivity and Sandell’s sensitivity were found to be 5.90 × 105 L mol-1 cm-1 and 0.00070 μg cm-2 for cypermethrin and 3.81 × 105 L mol-1 cm-1 and 0.0011 μg cm-2 for fenvalerate pesticides. The developed method has been satisfactorily applied for the determination of cypermethrin and fenvalerate in their formulations and various food, agricultural and biological samples.